Air pollution and health impacts during the COVID-19 lockdowns in Grenoble, France. (15th June 2022) - Aix, Marie-Laure; Petit, Pascal; Bicout, Dominique J.
Abstract: It is undeniable that exposure to outdoor air pollution impacts the health of populations and therefore constitutes a public health problem. Any actions or events causing variations in air quality have repercussions on populations' health. Faced with the worldwide COVID-19 health crisis that began at the end of 2019, the governments of several countries were forced, in the beginning of 2020, to put in place very strict containment measures that could have led to changes in air quality. While many works in the literature have studied the issue of changes in the levels of air pollutants during the confinements in different countries, very few have focused on the impact of these changes on health risks. In this work, we compare the 2020 period, which includes two lockdowns (March 16 - May 10 and a partial shutdown Oct. 30 - Dec. 15) to a reference period 2015–2019 to determine how these government-mandated lockdowns affected concentrations of NO2, O3, PM2.5, and PM10, and how that affected human health factors, including low birth weight, lung cancer, mortality, asthma, non-accidental mortality, respiratory, and cardiovascular illnesses. To this end, we structured 2020 into four periods, alternating phases of freedom and lockdowns characterized by a stringency index. For each period, we calculated (1) the differences in pollutant levels between 2020 and a reference period (2015–2019) at both background and traffic stations; and (2) the resulting variations in the epidemiological based relative risks of health outcomes. As a result, we found that relative changes in pollutant levels during the 2020 restriction period were as follows: NO2 (−32%), PM2.5 (−22%), PM10 (−15%), and O3 (+10.6%). The pollutants associated with the highest health risk reductions in 2020 were PM2.5 and NO2, while PM10 and O3 changes had almost no effect on health outcomes. Reductions in short-term risks were related to reductions in PM2.5 (−3.2% in child emergency room visits for asthma during the second lockdown) and NO2 (−1.5% in hospitalizations for respiratory causes). Long-term risk reductions related to PM2.5 were low birth weight (−8%), mortality (−3.3%), and lung cancer (−2%), and to NO2 for mortality (−0.96%). Overall, our findings indicate that the confinement period in 2020 resulted in a substantial improvement in air quality in the Grenoble area. Graphical abstract: Image 1 Highlights: Global level changes in 2020: NO2 (−32%), PM2.5 (−22%), PM10 (−15%) and O3 (+10.6%). Health risk impacts were mainly related to changes in PM2.5 and NO2 levels. Short-term risks of child asthma (−3%) and hospitalization for respiratory diseases (−2%). Long-term risks of low birth weight (−8%), mortality (−4%), and lung cancer (−2%).